Cross-sectional biomonitoring of urinary deoxynivalenol, T-2 and HT-2 toxins, and zearalenone in Japanese adults - Tajima, Toshiki; Isobe, Tomohiko; Saito, Isao; Kondo, Takaaki; Suzuki, Koji; Fujii, Ryosuke; Tsuboi, Yoshiki; Sugita-Konishi, Yoshiko; Ueyama, Jun (Environmental Health and Preventive Medicine, 2025)
Background: Among the more than 300 mycotoxins that are known to have toxic effects on animals and humans, Fusarium toxins deoxynivalenol (DON), T-2 and HT-2 toxins (T2/HT2), and zearalenone (ZEN) are frequently detected in domestic agricultural products. This study aimed to assess DON, T2/HT2, and ZEN exposure in Japanese adults by measuring urinary mycotoxins, observing their distributions, and making comparisons with data from other countries.Methods: A total of 201 individuals participated in the study. Twenty-four-hour urine samples were collected from young adults (34 men and 35 women) in the Tokai region (urban area) and spot urine samples were collected from middle-aged and elderly adults (64 men and 68 women) in the Donan area of Hokkaido Prefecture (rural area). Urinary DON, T2/HT2, and ZEN levels were measured using a validated liquid chromatography–tandem mass spectrometry method.Results: For DON, T2/HT2, and ZEN, the detection frequencies above the limit of detection (LOD) level (0.15, 0.13, and 0.01 µg/L, respectively) in all the samples were 53%, 26%, and 71%, respectively. The median concentrations (95th percentile) of urinary DON, HT2, and ZEN were 0.19 (3.93), <LOD (0.55), and 0.02 (0.12) µg/L, respectively. Although at least one of the investigated mycotoxins was detected in the urine of 86% of study participants, the concentrations were similar to or lower than those found in other countries (from 19 reports within the past decade). Moreover, the probable daily intake (PDI) values in the present study were lower than the provisional maximum tolerable daily intake levels. The urinary mycotoxin levels did not significantly differ with respect to sex, age, or occupation.Conclusions: This study represents the first comprehensive exposure assessment for DON, T2/HT2, and ZEN in Japanese adults using human biomonitoring methods. These data provide valuable information for a better understanding of mycotoxin exposure in Japan.